OPTIMALISASI WORDWALL SEBAGAI APLIKASI PEMBELAJARAN BERBASIS DIGITAL UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA Studi Kasus di SMPN 1 Ibun Kabupaten Bandung - Waska Warta; Susi Susanti; Asep Fauzi Amanu; Neneng Purwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The use of digital learning media is one strategy to increase student learning motivation. At SMPN 1 Ibun, students still experience low learning motivation due to a lack of varied learning methods and minimal use of interactive media. This study aims to provide an overview of Wordwall management as a digital learning application to support student learning motivation at SMPN 1 Ibun. The study used a descriptive qualitative approach, with data collection techniques through interviews, observation, and documentation. The conceptual framework refers to learning motivation theory and the principles of technology-based learning. Wordwall management was analyzed using the PDCA approach: the Plan stage, which involves planning the use of Wordwalls according to learning objectives; the Do stage, which involves implementing media in learning activities; the Check stage, which involves observing student engagement and responses, as well as descriptive questionnaire results; and the Act stage, which involves reflection and subsequent learning improvements. The results showed an increase in learning motivation indicators, such as increased student enthusiasm and activeness during learning. Thus, Wordwall management has the potential to create a more engaging learning environment and support student learning motivation on an ongoing basis.